First Successes and Failures of Universities Participating in “Leadership in the Region and/or Industry” Track of the “Priority 2030” Program - A. I. Guseva; V. M. Kalashnik; V. I. Kaminsky; S. V. Kireev (Высшее образование в России)
The article presents the results of quantitative indicators analysis of the main activities of three groups of universities participating in the “Priority 2030” program of the “Leadership in the region and/or industry” track (hereinafter referred to as the territorial and industrial track) during the first year of their development programs implementation. The Displaced Ideal Method was used in the research. Dynamics of indicators series of special and basic parts has being analyzed for universities groups in 2017-2021. The strengths and weaknesses of the universities groups of the territorial and industrial track are revealed. It was established that the special indicators values achieved by universities during the first year had a significant impact on the assessment of the Council for universities development programs support in frame of Priority-2030 Project, which taking into account the performances of the universities teams led to significant changes in the groups composition of the studied track – more than half of universities changed their positions. A number of reasons were considered that led to a change in universities’ positions in the groups of the researched track.